Aminoglycosides against carbapenem-resistant Enterobacteriaceae in the critically ill: the pitfalls of aminoglycoside susceptibility. Issue 6 (3rd June 2017) - Zavascki, Alexandre P.; Klee, Brandon O.; Bulitta, Jürgen B.
ABSTRACT: Introduction : The emergence of carbapenem-resistant Enterobacteriaceae (CRE) has brought aminoglycosides to the frontline since an aminoglycoside may be the only antimicrobial to which CRE isolates show in vitro susceptibility. The appropriateness of aminoglycoside-based therapies for severe infections by CRE is discussed considering the current breakpoints and recent pharmacokinetic (PK) studies in critically ill patients. Areas covered : Many aminoglycoside-susceptible CRE isolates present minimal inhibitory concentrations (MICs) at or slightly below the breakpoint of amikacin or gentamicin. However, recent PK studies with these aminoglycosides in critically ill have invariably shown that the PK/pharmacodynamic (PD) target is very unlikely attained even when high doses are administered, if the MICs are near the breakpoint. Expert commentary : While new antimicrobials are not widely available, the authors forecast an increasing use of aminoglycosides as backbone antibiotics against CRE isolates. However, the altered PK of aminoglycosides in critically ill patients severely impairs their predicted efficacy in these patients. Aminoglycoside breakpoints may hide 'aminoglycoside-susceptible' CRE isolates for that aminoglycosides will unlikely be effective if used in monotherapy. Therefore, these breakpoints may need to be revised due to the increasing use of aminoglycosides as backbone antibiotics to treat severe infections by CRE isolates in critically ill patients.